The collector - Silva, Daniel, 1960- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2023)
Legendary art restorer and spy Gabriel Allon joins forces with a brilliant and beautiful master-thief to track down the world's most valuable missing painting but soon finds himself in a desperate race to prevent an unthinkable conflict between Russia and the West.
Keywords: Allon, Gabriel -- (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Art restorers -- Fiction; Thieves -- Fiction; Thrillers (Fiction); Spy fiction